Sleep Apnea-A Review - Rajbhandari, Rajeeb (Nepalese Heart Journal, 2017)
Sleep apnea literally means “cessation of breath.” Sleep apnea is a common disorder in which we have one or more pauses in breathing or shallow breaths during our sleep. Breathing pauses can last from a few seconds to minutes. They often occur 5 to 30 times or more an hour. Typically, normal breathing then starts again, sometimes with a loud snort or choking sound. Sleep apnea usually is a chronic condition that disrupts sleep 3 or more nights each week. This results in poor sleep quality that makes one tired during the day. Sleep apnea is one of the leading causes of excessive daytime sleepiness. The airway can become obstructed at several possible sites like the excess tissue in the airway enlarged tonsils, a large tongue, the airway muscle which relaxes and collapses during sleep.